Inauguration of Technical Annals e-publishing - Stasinos George Ν. (Technical Annals, 2023)
With particular joy, respect and commitment to the history of TEE, to the future of the scientific role of the Chamber and to the work of Greek Engineers as a whole, the Technical Chamber of Greece is proceeding with the publication of an international scientific journal. After several years without regular scientific publications, due to the special economic situation of the country, but having as a source of our history the TECHNICAL ANNALS, published by the TEE for decades, we undertake this role again to give another scientific podium to the Engineering community.